P385 TREM1, the first anti-TNF specific biomarker guiding therapeutic decision. (25th January 2019) - Verstockt, B; Verstockt, S; Dehairs, J; Ballet, V; Blevi, H; Wollants, W-J; Breynaert, C; Van Assche, G; Vermeire, S; Ferrante, M
Abstract: Background: With the expanding therapeutic armamentarium for inflammatory bowel diseases (IBD), biomarkers predicting efficacy are urgently needed. To predict outcome to anti-TNF therapy, we studied whole blood and mucosal expression of genes previously reported to predict outcome to anti-TNF therapy, and investigated whether the signature was specific for these agents. Methods: We prospectively included 35 (discovery) and 19 (validation) consecutive IBD patients with active disease (both Crohn's disease and ulcerative colitis) initiating anti-TNF therapy, as well as 22 patients initiating ustekinumab and 51 patients initiating vedolizumab. Whole blood expression levels of OSM, TNF, TNFR2 and TREM1 (total and all individual transcripts separately) were measured prior to start of therapy using qPCR, and mucosal gene expression in inflamed biopsies using RNA-sequencing. Endoscopic remission was defined as an SES-CD ≤2 at Week 24 for Crohn's disease and a Mayo endoscopic sub-score ≤1 at Week 8–14 for ulcerative colitis. Results: Baseline whole blood TREM1 expression was significantly down-regulated in future anti-TNF healers ( p < 0.001, both discovery and validation cohort) (Figure). Abstract P385 Baseline whole blood TREM1 expression in relation to endoscopic remission later on in both the discovery and validation cohort, visualised by diagnosis. ** p < 0.005, *** p < 0.001. Receiver operator characteristic statistics showed an area under the curve (AUC) of 0.78 ( p = 0.001), resulting in post-test probabilities of 77.1% and 90.0% for endoscopic remission and non-remission, respectively. A similar accuracy could be observed in mucosal TREM1 expression (AUC 0.77, p = 0.003), which outperformed the accuracy of serum TREM1 at the protein level (AUC 0.58, p = 0.31). Whole blood TREM1 expression did not significantly correlate with CRP (Spearman = −0.08, p = 0.38), faecal calprotectin (Spearman = −0.06, p = 0.64) or serum TNF (Sspearman = −0.15, p = 0.63). OSM, TNF, and TNFR2 were not differentially expressed in whole blood ( p = 0.09, p = 0.13, p = 0.24, respectively), whereas they were at the mucosal level ( p = 0.007, p = 0.02, p = 0.008, respectively). The whole blood TREM1 predictive signal was anti-TNF specific, as no changes in expression were seen in ustekinumab and vedolizumab treated patients, neither in whole blood ( p = 0.82, p = 0.53, respectively), nor in tissue ( p = 0.24, p = 0.10, respectively). Conclusions: We identified and validated low TREM-1 as a specific biomarker for anti-TNF-induced endoscopic remission. These results can aid in the selection of therapy in biological-naïve patients, but should be confirmed in a randomised trial prior to translation into daily clinical practice.